Polymorphic analysis of field collected Aedes Albopictus from Subang Murni, Shah Alam using Internal Transcribed Spacer 2 (Its2) Rdna Marker / Nadiah Mohd Nawawi - Mohd Nawawi, Nadiah (2015)
The increase of dengue cases at an alanning rate in Malaysia has been strongly associated with Ae. aegypti and Ae. albopictus vectors. However, the fonner is always the subject of interest while the latter is often regarded as the secondary vector-despite its worldwide expansion. Studies examining the population genetics structure of Ae. albopictus are established, although most of the studies emphasised on the interpopulation genetic diversities using mitochondrial genome markers. Hence, this study was conducted to evaluate the intrapopulation and interpopulation genetic polymorphisms in Ae. albopictus from dengue infested area, Subang Murni, Shah Alam, Malaysia using nuclear DNA marker. Ovitraps used to collect Ae. albopictus eggs were placed at random in the study area and the eggs were reared to adults in the laboratory. The genomic DNA of five individuals and one pooled sample of Ae. albopictus from Subang Mumi was obtained and analysed for polymorphism at ITS2 region of ribosomal DNA. 337 bp of PCR products was obtained and sequenced. The sequences were subjected to BLAST and showed high similarities with homologous sequences from NCBI GenBank. Subsequently, the nucleotide sequences were aligned using ClustalX2.1 software. Phylogenetic tree inferred using maximum likelihood method in MEGA5.2 revealed that Ae. albopictus population from Subang Murni genetically differs from each other although they were from the same locality. Nevertheless, this population has shown unifonn homogeneity when compared with other worldwide populations namely Italy, United States, Japan, China and Greece. This is true except for a particular strain from Subang Mumi that was separated in another group together with populations from Italy and Subang Jaya, Malaysia. These findings deduced that there is higher genetic variation within population of the same locality compared to variation at geographical differences. This infonnation may be beneficial to construct the appropriate level of surveillance and control measures needed to prevent the future expansion of this vector and simultaneously reduce the health risks. Keywords: Aedes albopictus, Malaysia, ITS2, genetic polymorphism